Effect of Motivation on Basic School Teachers’ Performance in the Ajumako Enyan Esiam District: Implications for Bridging the Relationship Gap among Adult Employees - Pajibo, Edison D.; Asante, Herty; Dzikunu, Cosmos Kwame (Global Journal of Social Sciences Studies, 2020)
This study sought to assess the effect of motivation on basic school teachers’ performance in Ajumako Enyan Esiam District and the implications for bridging the relationship gap among adult employees. A triangulation concurrent mixed method design was used with a total sample of 135 respondents including teachers, head teachers, school management committee executive (SMC) and the District Director of Education. The data was collected using structured questionnaires, focus group discussion and interview. Data was analyzed using descriptive and inferential statistics. Focus group discussion for headteachers, school management executive and interview for the Director of Education were presented in themes. Research findings revealed that, the performance of teachers was average despite the fact that, their motivation was inadequate. Besides, majority of the teachers performed their activities with high morale as evidenced by regular tests and examinations of pupils and supervision of all school activities. A significant positive relationship between intrinsic motivation and performance of teachers was found to exist in basic schools in the Ajumako Enyan Esiam District. Another, a positive relationship was also found between extrinsic motivation and performance of teachers, implying that extrinsic motivation affected the performance of teachers. In order to improve teacher motivation and performance at work and to strengthen the relationship between teachers and head teachers (employees), the study recommended increase in the remuneration of basic school teachers to match the increased cost of living, provision of accommodation to teachers, strengthening of supervision as well as instituting awards for good performance and provision of TLMs.